Resource recovery from urban waste: options and challenges for community based composting in Sub-Saharan Africa - Cofie, Olufunke O.; Drechsel, Pay; Agbottah, S.; Veenhuizen, René van (2008)
Municipal authorities in developing countries are facing immense challenges in managing both solid and liquid waste in a sustainable way. Recycling is not yet high on their agenda although they appreciate the potential of composting for waste volume reduction. This offers an entry point to introduce organic waste recycling as a component of sustainable integrated sanitation which has the potential of a win-win situation by reducing waste flows, ensuring environmental health, supporting food production and creating livelihoods. However, due to several constraints recycling attempts have often a short life time. This paper tries to analyse related reasons by drawing from a larger feasibility study in Ghana and a survey of compost stations in different parts of Africa. It concludes with a framework for the analysis and the planning of recycling interventions in the context of sustainable sanitation, looking in particular at community based options for solid waste and human excreta.